INDUCTION OF MICROCYTIC-HYPOCHROMIC ANAEMIA IN Clarias gariepinus (BURCHELL, 1822) EXPOSED TO SUB-LETHAL CONCENTRATIONS OF 1, 1-DIMETHYL 4, 4-BIPIRIDILLIUM DICHLORIDE (PARAQUAT) UNDER LABPRATORY CONDITIONS (FULafia Journal of Science and Technology, 2023)
Microcytic-hypochromic anaemia was induced in Clarias gariepinus (Burchell, 1822) at intervals of 1, 7 and 14 days. Experimental fish were exposed to test water separately diluted with sub-lethal concentrations of paraquat of 0, 0.06, 0.07, 0.09 and 0.12mg/L. 14 days’ exposure to the sub-lethal concentrations of the toxicant resulted in mirocytic-hypochromic anaemia in the exposed fish. Blood indices attributable to mirocytichypochromic anaemia was observed with a significant (p
Keywords: Toxicity, paraquat; Clarias gariepinus; microcytic-hypochromic; anaemia